Analisis Face Recognition Boarding Gate Sebagai Inovasi Peningkatan Kualitas Pelayanan Publik pada PT. Kereta Api Indonesia (Persero) DAOP II Bandung - Aprilia, Firda; Ravenska, Nanda; Putrianti, Septiana Dwi; Harahap, Anggi Syahadat (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2024)
PT. Kereta Api Indonesia (Persero) as a company engaged in the field of public transportation services certainly has a duty to be able to provide the best service to all service users. One form of digital transformation innovation that is being carried out is by innovating KAI's face recognition boarding gate as an effort to improve the quality of service at the Station. For this reason, this study aims to see and analyze the extent of incremental innovation and service quality from the implementation of the KAI face recognition boarding gate innovation at Bandung Station. The research method used is descriptive research with a qualitative approach, with the type of case study research. From the research results it can be seen that the incremental innovation carried out by PT. Kereta Api Indonesia (Persero) has met the indicators of sustainable management method innovation, continuous process innovation, and sustainable technological innovation. From the research results, the services provided by the face recognition boarding gate officers at the Bandung Station have fulfilled the service dimensions which include the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. There are also things that need to be done by the company, among others, maximizing the face recognition registration process through the KAI application by using the liveness detection stage and socializing usage through social media to attract audiences and increase the number of users.